Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1590/0037-8682-0272-2018
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of diagnostic-therapeutic strategies for visceral leishmaniasis in Brazil

Abstract: Introduction: Visceral leishmaniasis (VL) is fatal if not diagnosed and treated. This study aimed to estimate the cost-effectiveness of diagnostic-therapeutic alternatives for VL in Brazil. Methods: A decision model estimated the life expectancy and costs of six diagnostic-therapeutic strategies. Results: IT LEISH + liposomal amphotericin B emerged the best option, presenting lower costs and higher effectiveness. DAT-LPC + liposomal amphotericin B showed an incremental cost-effectiveness ratio of US$ 326.31 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…WHO evaluated some of the commercially available tests: DiaMed-IT LEISH (Bio-Rad Laboratories), Crystal R KA (Span Diagnostics Ltd.), Signal R -KAb (Span Diagnostics Ltd.), Kalazar Detect TM (InBios International Inc.), and Onsite Leishmania Ab Rapid Test (CTK Biotech Inc.). Other tests are also on the market: IT LEISH (Bio-Rad Laboratories), rK39-ICT (SD BIOLINE Leishmania Ab, Standard Diagnostics, Inc., South Korea), and Rapydtest (Diagnostic International Distribution S.p.A, Milan, Italy) (Brandonisio et al, 2002;Carvalho et al, 2003;World Health Organization, 2010b;Cota et al, 2013;Varani et al, 2017;Bangert et al, 2018;Assis et al, 2019;Freire et al, 2019). ICTs have been tested mainly for the diagnosis of anthroponotic leishmaniasis and less frequently for zoonotic leishmaniasis (Boelaert et al, 2014).…”
Section: Immunochromatic Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…WHO evaluated some of the commercially available tests: DiaMed-IT LEISH (Bio-Rad Laboratories), Crystal R KA (Span Diagnostics Ltd.), Signal R -KAb (Span Diagnostics Ltd.), Kalazar Detect TM (InBios International Inc.), and Onsite Leishmania Ab Rapid Test (CTK Biotech Inc.). Other tests are also on the market: IT LEISH (Bio-Rad Laboratories), rK39-ICT (SD BIOLINE Leishmania Ab, Standard Diagnostics, Inc., South Korea), and Rapydtest (Diagnostic International Distribution S.p.A, Milan, Italy) (Brandonisio et al, 2002;Carvalho et al, 2003;World Health Organization, 2010b;Cota et al, 2013;Varani et al, 2017;Bangert et al, 2018;Assis et al, 2019;Freire et al, 2019). ICTs have been tested mainly for the diagnosis of anthroponotic leishmaniasis and less frequently for zoonotic leishmaniasis (Boelaert et al, 2014).…”
Section: Immunochromatic Testsmentioning
confidence: 99%
“…Regarding the WHO results for the zoonotic VL due to L. infantum in Brazil, the best sensitivity was obtained for DiaMed-IT LEISH (Se: 92%) whereas the best specificity was for Signal R -KAb (Sp: 98.8%) (World Health Organization, 2010b). A study in Brazil assessed cost-effective strategies, and found that VL diagnosis by ICT followed by treatment with amphotericin B (liposomal formulation) is less expensive with high effectiveness (Assis et al, 2019). During outbreaks, this assay is very convenient at the point of care facilities for rapid identification of cases (Bangert et al, 2018).…”
Section: Immunochromatic Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carvalho et al 3 evaluated the total cost of visceral leishmaniasis care in Brazil in 2014, which was US$14 million, with total medical costs of approximately US$1.9 million. 3,4 Factors that reduce morbidity and mortality and consequently the impact of the two clinical presentations of the disease are an early diagnosis and the initiation of appropriate specific treatment. [5][6][7][8] In this scenario, the introduction of new information and communication technologies (ICTs) that can help health professionals with the early diagnosis and appropriate treatment, even in remote endemic areas, is necessary.…”
Section: Introductionmentioning
confidence: 99%